Nanohybrids from nanotubular J-aggregates and transparent silica nanoshells1. Issue 60 (4th August 2015) - Qiao, Yan; Polzer, Frank; Kirmse, Holm; Kirstein, Stefan; Rabe, Jürgen P.
<x xml:space="preserve">Abstract</x> Organic–inorganic nanohybrids were synthesized by coating supramolecular tubular J-aggregates with helically wound silica ribbons, which significantly enhance the stability of J-aggregates.